The Effectiveness of the Raskin Policy and Household Food Security in Medan Sinembah Village, Tanjung Morawa District, Deli Serdang Regency - Muhammad Ari Fazlur (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2020)
In 2002 the government created a program for poverty alleviation in Indonesia, namely Rice for the Poor or commonly called RASKIN. The government budget for Raskin is Rp. 9.98 trillion. Medan Sinembah Village is one of the villages in Tanjung Morawa District with a population of 7,589 people and 560 households receiving Raskin. So a sample of 85 families was taken by comparative testing, so the results obtained that the effectiveness of Raskin recipients for poor families in Medan Sinembah Village was greatly helped by the Raskin program provided by the government in increasing household food security for the Medan Sinembah village community.